Evaluation of the rapid diagnostic test SDFK40 (Pf-pLDH/pan-pLDH) for the diagnosis of malaria in a non-endemic setting - Maltha, Jessica (BioMed Central, 2011)
BACKGROUND: The present study evaluated the SD Bioline Malaria Ag 05FK40 (SDFK40), a three-band RDT detecting Plasmodium falciparum-specific parasite lactate dehydrogenase (Pf-pLDH) and pan Plasmodium-specific pLDH (pan-pLDH), in a reference setting. METHODS: The SDFK40 was retrospectively and prospectively tested against a panel of stored (n = 341) and fresh (n = 181) whole blood samples obtained in international travelers suspected of malaria, representing the four Plasmodium species as well as Plasmodium negative samples, and compared to microscopy and PCR results. The prospective panel was run together with OptiMAL (Pf-pLDH/pan-pLDH) and SDFK60 (histidine-rich protein-2 (HRP-2)/pan-pLDH). RESULTS: Overall sensitivities for P. falciparum tested retrospectively and prospectively were 67.9% and 78.8%, reaching 100% and 94.6% at parasite densities >1,000/μl. Sensitivity at parasite densities ≤ 100/μl was 9.1%. Overall sensitivities for Plasmodium vivax and Plasmodium ovale were 86.7% and 80.0% (retrospectively) and 92.9% and 76.9% (prospectively), reaching 94.7% for both species (retrospective panel) at parasite densities >500/μl. Sensitivity for Plasmodium malariae was 21.4%. Species mismatch occurred in 0.7% of samples (3/411) and was limited to non-falciparum species erroneously identified as P. falciparum. None of the Plasmodium negative samples in the retrospective panel reacted positive. Compared to OptiMAL and SDFK60, SDFK40 showed lower sensitivities for P. falciparum, but better detection of P. ovale. Inter-observer agreement and test reproducibility were excellent, but lot-to-lot variability was observed for pan-pLDH results in case of P. falciparum. CONCLUSION: SDFK40 performance was poor at low (≤ 100/μl) parasite densities, precluding its use as the only diagnostic tool for malaria diagnosis. SDFK40 performed excellent for P. falciparum samples at high (>1,000/μl) parasite densities as well as for detection of P. vivax and P. ovale at parasite densities >500/μl.